Isolation, identification and investigation of genetic diversity of Lactobacillus bacteria strains in traditional dairy products of Lorestan province (Iran). - Samiei, Kamran; Bahrami, Razieh; Doosti, Bhrooz (Indian Journal of Dairy Science, 2025)
Traditional dairy products contain a diverse set of bacteria that produce useful biological compounds called bacteriocins. Lorestan province is rich in natural flora due to its special ecosystem and traditional dairy products. In this regard, in order to isolate, identify and investigate the genetic diversity of Lactobacillus bacteria found in dairy products, 10 samples from each of the traditional yogurt, dough and cheese products of Lorestan province were collected and evaluated. Primary bacteria were isolated using special culture medium (MRS) and various biochemical tests including gram test, catalase test and antibiogram test. In the next step, in order to confirm and identify the isolated bacteria, 16SrRNA gene amplification and sequencing were used. After identifying the bacteria, the genetic diversity between the isolated bacterial strains was evaluated using REP-PCR and BOX-PCR genetic markers. The antibiogram test showed that all isolated bacterial strains were resistant to vancomycin and kanamycin and sensitive to gentamicin. After the amplification of 1500 base pairs of 16SrRNA gene and its evaluation in databases, it was found that the strain isolated from the dairy products yogurt, dough and cheese were the most similar to L.casei, L.fermentum and L.helveticus bacteria respectively. The grouping of the studied bacterial strains based on the similarity matrix of the combination of two markers showed that the studied bacteria formed 7 groups at a similarity coefficient of 45%, and the bacteria isolated from Noorabad local yogurt formed only one group. The results of the present study showed the high potential of traditional dairy products of Lorestan province in terms of having probiotic strains with high genetic diversity, which can be considered as suitable biological preservatives and used for the production of various dairy products commercially.